The Knowledge about Personal Hygiene Relationship with Preventive Behavior of Flour Albus in Young Women in Taeng Village, Pallangga District - Aulia Mutmainnah; Agustina Ningsi; Wirawati Amin; Hj Indriani (Media Kesehatan Politeknik Kesehatan Makassar, 2021)
Adolescence is a period of transition from childhood to adulthood which undergoes changes both physically and psychologically. Adolescent girls are susceptible to infection of reproductive organs, especially flour albus due to lack of good personal hygiene behavior. Therefore, adolescents must be prepared with both knowledge and preventive behavior to achieve healthy reproduction. The purpose of this study was to determine the relationship between knowledge about personal hygiene and the behavior of preventing flour albus in adolescent girls in Taeng Village, Pallangga District. Samples were taken from primary data, unmarried young women aged 12-25 years in Taeng Village, RW 004, Pallangga District, many as 98 people. The research design used descriptive analytic with a cross-sectional approach. The results in this study showed that respondents who had good knowledge were 42 respondents, of which 90.5% had good behavior in preventing flour albus and 9.5% had poor behavior in preventing flour albus. While respondents who have less knowledge are 7 respondents, where there are 28.6% who have good behavior in preventing flour albus and 71.4% who have poor behavior in preventing flour albus. The results of statistical tests with Chi-square obtained a value of = 0.001. The conclusion in this study is that there is a relationship between knowledge about personal hygiene and the behavior of preventing flour albus in adolescent girls in Taeng Village, Pallangga District. Therefore, it is recommended for young women to increase their knowledge by reading books or looking for information on the internet about personal hygiene in the prevention of vaginal discharge and can also ask directly to teachers or parents so that appropriate and correct information about genital personal hygiene is obtained. Keyword                : Behavior, Flour Albus, Knowledge, Personal HygieneReference              : 26 (2008-2021)